Enhancement of wind turbine performance by installation above a bluff body - Goh, Ernest Seach Chyr (2015)
When a bluff body is exposed to wind resulting in flow over a forward facing step, the flow field above the bluff body consists of a circulating separation bubble. The wind velocity within this bubble varies from being negative (opposite in direction to the free stream wind) near the top surface of the bluff body, to near zero at the centre of the bubble, to high positive in the top part of the bubble before gradually reducing to the free stream wind speed far away from the surface. The high positive wind velocity in this flow field can be exploited to boost wind turbine power output. The present research has discovered that when optimally installed with axis horizontal, a two-bladed Savonius turbine above an infinitely wide step has a coefficient of power (cP, calculated using the free stream wind speed) which is 2.6 times the cP of an identical turbine operating in an unbounded airspace. The optimal turbine installation position is at 0.56H above the top surface in the vertical direction and 0.75H behind the front edge in the horizontal direction, where H is the step height. Extending from this optimal point is a line of optimal installation position. For a flow over a forward facing step, a line of minimum wind speed, generally passing through the middle of the separation bubble can be extracted from the flow field. The line of optimal installation position is similar in shape to this line of minimum wind speed but offset above it. The methodology used in the present research consists primarily of Computational Fluid Dynamics (CFD) parametric simulation covering a range of installation positions and turbine tip speed ratio (TSR). The commercial solver ANSYS CFX in the workbench environment was used. Validation of the simulation results were carried out using data from driving tests of a test rig mounted on a lorry driven at a range of speeds. The test rig consists of a Savonius turbine installed above a bluff body. During the design of the test rig, wind tunnel tests and supporting CFD simulations were used to determine the turbine position that is likely to give maximum power output. As a result of the driving tests, practical experience was gained which will be useful for future researchers.